(untitled) (Journal of Hama University, 2022)
This study aims to compare effect of methotrexate and cyclosporine in decreasing the ocular complications of bechet s disease which is an chronic inflammatory disease characterIzed by a replapsing and remitting course .It manifests oral and genital ulcerations, skin lesions, uveitis and others organ involvement. Its prevalence is the highest in the middle east, uvietes is the premier effective in 35%, 55 patiants 40 meles 15 fememles. The moderate age was 32.5 years, The visual acuity corrected in the group of methotrexate after 2.5 years is 0.6±0.4. The viual acuity corrected in the group of cyclosporine is 0.5±0.2, metotrixate is plus effective in the decrease of the inflammatory and increase of remitting course.